Influence of Depletion Transition Layers on Surface Polaritons in Semiconductor Films - Beletskij, N. N.; Gasan, E. A. (Видавничий дім «Академперіодика», 2012)
Influence of Depletion Transition Layers on Surface Polaritons in Semiconductor Films